1989
DOI: 10.1021/bi00447a048
|View full text |Cite
|
Sign up to set email alerts
|

A simple model for proteins with interacting domains. Applications to scanning calorimetry data

Abstract: A simple thermodynamic model is formulated for the purpose of interpreting scanning calorimetry data on proteins that have interacting domains. Interactions are quantified by inclusion of an interface free energy, delta GAB, in the thermodynamics of unfolding for multidomain proteins. The assumption is made that delta GAB goes to zero with the unfolding of either domain involved in pairwise interaction, so the interaction term appears to stabilize only the domain with the lower TM. Application of the model to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
208
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(226 citation statements)
references
References 29 publications
17
208
1
Order By: Relevance
“…This suggests that domain interactions are weakened by reducing hydrophobic contacts or by placing a polar side chain into the hydrophobic interface. Further In the given context, Brandts et al (1989) developed a thermodynamic model that explains the stability of multi-domain proteins as the sum of increments of the separate domains plus contributions of the domain-domain interactions. Hence, if the less stable domain unfolds, its contribution to the stability of the more stable domain disappears.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that domain interactions are weakened by reducing hydrophobic contacts or by placing a polar side chain into the hydrophobic interface. Further In the given context, Brandts et al (1989) developed a thermodynamic model that explains the stability of multi-domain proteins as the sum of increments of the separate domains plus contributions of the domain-domain interactions. Hence, if the less stable domain unfolds, its contribution to the stability of the more stable domain disappears.…”
Section: Discussionmentioning
confidence: 99%
“…According to the above model, which describes the stability of domain proteins as the sum of increments (Brandts et al, 1989), two extremes can be visualized: (i) Domains that unfold as independent entities will exhibit the same intrinsic stability, irrespective of whether they are isolated as separate "modules," or covalently linked (cf. Missiakas et al, 1990;Markovic-Housley et al, 1994); and (ii) if cooperative interactions between domains are essential for the intrinsic stability of the domains, folding and unfolding are strictly coupled so that the complete protein behaves as a single cooperative unit (cf.…”
Section: Discussionmentioning
confidence: 99%
“…This result is contrary to what is generally observed for the unfolding of proteins with interacting domains. Theoretical models generally account for painvise domain-domain interactions by using a favorable interface free energy that goes to zero when one of the domains unfolds (Brandts et al, 1989;Freire et al, 1992). These models have been successful in explaining the unfolding properties of several proteins with domains communicating by painvise interactions.…”
Section: Discussionmentioning
confidence: 99%
“…As soon as one domain unfolds, the stabilizing effect of the complex formation vanishes, and, as a consequence, the second chain starts to unfold as well. For protein folding in cells, and thus for expression, however, the presence of one stably folded domain to serve as nucleation point for a less stable chain could be sufficient to substantially increase the amount of 36 In fact, studies have revealed that CH1 requires the interaction with the folded constant LC region controlling the assembly of the full-length antibody in vivo. 37 In addition, pairing of the variable domains increases the stability of the variable LC domain due to interface contacts.…”
Section: Discussionmentioning
confidence: 99%